Mudarabah Perspektif Kaidah Fikhiyah - Deny Irawan (University of Darussalam Gontor, 2015)
The Mud a> rabahsystem has attracted the investors, either domestic or overseas. Various kind of product developments of mud a> rabahbegan to emerge, starting from financing to issuance of bond certificates and Certificate of mud a> rabah Investment among the Banks. National Sharia Council (DSN-MUI) as a supervisor for the implementation of Islamic economic system has an important role in maintaining the harmony of Islamic economic practice as rooted in Al-Qur’an and Sunnah. As fatwa is always required, some rules of Fiqh has been emerged